An Analysis of Cultural Value In Buya Hamka Movie - Ependi, Selviyan; Pradana, Ami; Putra, Dhanu Ario (Jurnal Penelitian Multidisiplin Bangsa, 2025)
Cultural values are not only habits that exist within the scope of society, but also found in movies. In this study, the researcher aimed to find various categories of cultural value based  on Buya Hamka movie. Data collection and completion analysis using qualitative descriptive research. The data taken is also based on the cultural values spoken or performed by Buya Hamka. Researchers have found 45 Cultural Values of Human Relations with God, 36 Cultural Values of Human Relations with Others, 8 Cultural Values of Human Relations with Society, 12 Cultural Values of Human Relations with Self And researchers found the Implications of Cultural Values Found in Education Sector, namely 36 Islamic values, 8 national values, 24 moral and ethical values and 4 cultural values Then the most dominating cultural value in the film is the Cultural Value of Human Relations with God and the Implications of Cultural Values in Buya Hamka's Education Sector, found mostly Islamic values. The researcher hopes that this study can be significant data for the linguistic community and can add insight to readers about the cultural values spoken and performed by Buya Hamka in the movie Buya Hamka.